Isolation, identification and treatment of Vancomycin-Resistant Staphylococcus epidermidis - T. Flayyih, May; K.Abd rabaa, Mariam (Iraqi Journal of Science, 2023)
Out of Hundred clinical samples, taken from different sources include burn, blood , wound and nasal swabs infections ; 90 isolates developed growth on mannitol salt agar. Among these, 40 (44.4%) were Coagulase positive (Staphylococcus aureus) isolates and 50 (55.5%)belong to coagulase negative staphylococci, in which the last Staphylococcus epidermidis isolates were 30(60%).Antibiotic susceptibility of Staphylococcus epidermidis isolates to 12 antibiotics were determined using disc diffusion method . The results revealed that high resistance to Penecillin G10 and Amoxiclav (Amoxicillin- clavulanic acid) ( 100%) and the high sensitivity to Imipenim (95%). The pattern of minimum inhibitory concentration of S.epidermidis isolates to vancomycin , was determined using MIC method; The results revealed that 12 S.epidermidis isolates ( 40 %) were vancomycin resistant, the MIC of them between (256- 32 μg) , 4 S.epidermidis isolates (13.3%) were intermediate resistance , the MIC to 3 of them were 16 μgand the last was 8 μg.